Penerapan Metode Metode Multy Attribute Utility Theory (MAUT) dalam Pemilihan Asisten Laboratorium Komputer - Rima Tamara Aldisa; Sanwani Sanwani; Deby Monalisa Simanjuntak; Sarpita Laia; Mesran Mesran (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Computer Laboratory Assistant is a person who is competent in the field of computers who will assist lecturers in teaching while in the computer laboratory. The Faculty of Computer Science, Budi Darma University, Medan will conduct a selection of computer laboratory assistants for the 2022/2023 academic year, but the lecturers have difficulties in finding which students are eligible to become computer laboratory assistants. This research is based on these reasons, so the authors decided to use the Multi Attribute Utility Theory (MAUT) method to help make decisions to choose which students deserve to be computer laboratory assistants with the criteria of GPA, test scores, personality, teaching ability and experience with a number of alternatives 5 (Five) students. The use of the MAUT method is expected to determine the criteria for computer laboratory assistants, because the MAUT method will perform a ranking process based on attributes with different weights so that the results are more optimal, then a ranking process will be carried out which will determine the optimal alternative as well. As for 1 (one) alternative that deserves to be a computer laboratory assistant is Jesika Sirait with a result of 0.4085.